Everyday Functioning in a Community-Based Volunteer Population: Differences Between Participant- and Study Partner-Report - Verrijp, Merike; Dubbelman, Mark A.; Visser, Leonie N. C.; Jutten, Roos J.; Nijhuis, Elke W.; Zwan, Marissa D.; van Hout, Hein P. J.; Scheltens, Philip; van der Flier, Wiesje M.; Sikkes, Sietske A. M. (Frontiers in Aging Neuroscience, 2022)
INTRODUCTION: Impaired awareness in dementia due to Alzheimer’s disease and related disorders, made study partner-report the preferred method of measuring interference in ‘instrumental activities of daily living’ (IADL). However, with a shifting focus towards earlier disease stages and prevention, the question arises whether self-report might be equally or even more appropriate. This study aims to investigate how participant and study partner report IADL perform in a community-based volunteer population without dementia, and which factors relate to differences between participant and study partner report. METHODS: Participants (N=3288; 18–97 years, 70.4% females) and their study partners (N=1213; 18–88 years, 45.8% females) were recruited from the Dutch brain research registry. IADL was measured using the Amsterdam IADL Questionnaire. Concordance between participant and study partner-reported IADL difficulties was examined using intraclass correlation coefficient (ICC). Multinomial logistic regressions were used to investigate which demographic, cognitive and psychosocial factors related to participant and study partner differences, by looking at the over- and underreport of IADL difficulties by the participant, relative to their study partner. RESULTS: The vast majority of A-IADL-Q scores represented no difficulties for both participants (87.9%) and study partners (89.4%). Concordance between participants and study partners was moderate (ICC=.55, 95%CI=[.51, .59]), 24.5% (N=297) of participants overreported their IADL difficulties compared to study partners, and 17.8% (N=216) underreported difficulties. The presence of depressive symptoms (odds ratio (OR)=1.31, 95%CI=[1.12, 1.54]), as well as memory complaints (OR=2.45, 95%CI=[1.80, 3.34]), increased the odds of participants overreporting their IADL difficulties. Higher IADL ratings decreased the odds of participant underreport (OR=0.71, 95%CI=[0.67, 0.74]). CONCLUSION: In this sample of community-based volunteers, the majority of participants and study partners reported no major IADL difficulties. Differences between participant and study partner were, however, quite prevalent, with subjective factors indicative of increased report of IADL difficulties by the participant in particular. These findings suggest that self- and study partner-report measures may not be interchangeable, and that the level of awareness needs to be taken into account, even in cognitively healthy individuals.